The Role of School Personnel in Implementing Guidance and Counseling in the Era of Globalization - Anissa; Firman; Neviyarni S (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
The global era as a new paradigma implies two main things, namely Internationalization Competition and Internationalization Links. What is needed to answer this global challenge lies in the quality of human resources, where individuals are required to think globally by acting and thinking quickly. What is no less important is the mentality of competing internationally by changing the role from spectator to player. Carrying out guidance and counseling management in accordance with developments in the era of globalization, the quality of human resources or the competency of counselors needs to be increased, sensitive to opportunities and responsive to global challenges and the need for cooperation between counselors and school personnel. The successful implementation of guidance and counseling management in schools cannot be separated from the cooperation of all school personnel. The success of counseling can support the achievement of educational goals for students at school. This research method is literature study. Data collection is carried out through a number of data libraries, recording and managing research materials. Based on the results of the research conducted, it shows that the collaboration carried out by the principal, homeroom teacher and class teacher in implementing guidance and counseling management at school has not been optimal. One of them can be seen from the cooperation of school personnel in providing or receiving input and suggestions, exchanging ideas or discussing openly.